Use of facilities of auxiliary character in the process of preparation of basketball players of agrarian higher educational establishments to allukrainian competitions - Teschuk L.I (Kharkov National Pedagogical University, 2012)
Application of exercises of a different orientation in the training process of basketball players of agrarian Institutes of higher on the stage of preparation to competitions is considered. It is shown that in the process of preparation of basketball players exercises of track-and-field orientation are unspecific, exercises of fitness, aerobics, acrobats, power exercises and swimming. Data of education and training process of basketball players of the national agrarian university of Belaya Tserkov are used in research, is analysed and generalized pedagogical experience of coaches of agrarian Institutes of higher. It is set, that in the structure of training process of basketball players have greater specific gravity the mean of track-and-field orientation.